Formation of professional competencies of EFL teachers in pandemic period - Turlybekov, B.; Yermekbayeva, A. (KU Publ., 2022)
A study about teaching competencies is discussed in various scientific research around the world. Especially it takes its momentum during the pandemic period. An approximation of the competencies advocating excellent and effective teaching profiles should be put into practice by linguistic education teachers. To achieve this goal, two actions were taken: a review of the frameworks for professional teaching generally and the role of teachers’ lab-based teaching showing their competencies to teach the English language at general education establishments in Kazakhstan. The recent pandemic period showed the relevant need to upgrade teachers’ qualifications and self-development. An observation of the conditions of the soft model realization was tested by research conducted by the authors. The conditions of three types were presented: content-activity, organizational- managerial, and the ability to transform the conditions of the first and second types for professional development of the teachers. The world keeps an extreme pace of remote-classroom activities nowadays, therefore it demands a model of a teacher who can adapt to changes and display creative leadership while building reciprocal relationships with learners throughout the teaching-learning process.
Пандемия кезеңінде ағылшын тілін шетел тілі ретінде оқытатын мұғалімдердің кәсіби құзыреттілігін қалыптастыру
Формирование профессиональных компетенций преподавателей английского языка как иностранного в пандемический период
Keywords: teaching competence; pandemic period; soft platform; online mektep; learning format; school teachers; distance learning; teaching content; professional competence